Efek Perawatan Metode Kangguru Terhadap Kenaikan Berat Badan pada Bayi Berat Lahir Rendah - Ita Herawati; Nofa Anggraini (Poltekkes Kemenkes Surakarta, 2020)
Background: The number of cases of low birth weight is still quite high, 15% of the 20 million babies worldwide are born with low birth weight every year. Low birth weight conditions need to be a concern because it can cause health complications. Aim to Analize the effect of kanggoro method to increase baby's weight of low birth weight. Methods: The experimental research design used was a static pre- posttest control group design with a case control approach, namely research by grouping or classifying intervention groups against the control group. The type of statistical test used in this study is the t test (t test). we performed 30 of low birth weight babies as a case of kangaroo care for 7 days and as control were 60 low birth weight babies, were only treated according to the hospital standart procedure,like ASI, parenterally and the drugs needed. Results: The average weight gain of infants who were intervened by the kangaroo method was 30.2 grams with a standard deviation of 11.79 grams, while for infants who were not intervened by the kangaroo method, the average baby's weight gain was only 15.5 grams with a standard deviation of 8,57 grams. Statistical test results obtained p = 0,000. Conclution: there were significant differences in the average weight gain of infants who were intervened by the kangaroo method and those who were not intervened by the kangaroo method.